Statins and Inflammation - Satny, Martin; Hubacek, Jaroslav A; Vrablik, Michal (Current atherosclerosis reports, 2021)
PURPOSE OF REVIEW: Chronic inflammation has been recognized as one of the most important pathophysiological mechanisms' initiation and progression of atherosclerosis. Statins belong to most successful therapeutic agents in the prevention and treatment of atherothrombotic vascular disease. Their non-lipid related effects including suppression of inflammation have been repeatedly proven in both experimental and clinical settings. RECENT FINDINGS: Recently, the importance of inflammation in the process of atherosclerosis has been confirmed by interventions targeting inflammation selectively. Clinical trial with selective inhibitor of a principal inflammatory mediator interleukin 1-beta - canakinumab - confirmed the notion of direct vasculoprotective effects of primarily targeting inflammation. This has increased interest in the non-lipid, pleiotropic and, particularly, anti-inflammatory effects of statins. Anti-inflammatory effects of statins have been proven both experimentally and in clinical settings beyond any doubt. They comprise a direct positive effect on not only many cell types and pathways that are lipid independent but, also, some that are mediated by lipid modification. Undoubtedly, suppression of inflammatory response by statins contributes to their generally positive action in atherosclerosis and represents an important part of the vasculo- and atheroprotective effect of this drug class.
Keywords: ateroskleróza; lidé; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Inflammation; Pleiotropy; Biomarkers; Atherosclerosis; zánět; statiny; Endothelial function; Statins; Humans; Cardiovascular